2019
DOI: 10.1017/s1368980019002349
|View full text |Cite
|
Sign up to set email alerts
|

Greater adherence to a Mediterranean-like diet is associated with later breast development and menarche in peripubertal girls

Abstract: Objective:To examine adherence to a Mediterranean-like diet at age 9–10 years in relation to onset of breast development (thelarche) and first menstruation (menarche).Design:We evaluated the associations of adherence to a Mediterranean-like diet (measured by an adapted Mediterranean-like Diet Score, range 0–9) with thelarche at baseline, age at thelarche and time to menarche. Data were collected at baseline during a clinic visit, complemented with a mailed questionnaire and three 24 hour telephone dietary reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Our findings are thus in line with previous prospective observational studies focusing on single nutrients and food groups, which suggested that higher intakes of fiber [ 22 ] or isoflavones [ 23 ], or lower meat [ 11 , 12 ] or SSB [ 19 , 20 ] consumptions were associated with a later timing of menarche. Previous studies have suggest that diet rich in fiber and isoflavones may delay timing of puberty by increasing sex hormone-binding globulin and decreasing endogenous estrogens [ 28 , 45 ] among girls. Conversely, intake of SSB may contribute to high levels of insulin secretion and insulin-like growth factor1 (IGF-1), which could result in early onset of puberty [ 19 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are thus in line with previous prospective observational studies focusing on single nutrients and food groups, which suggested that higher intakes of fiber [ 22 ] or isoflavones [ 23 ], or lower meat [ 11 , 12 ] or SSB [ 19 , 20 ] consumptions were associated with a later timing of menarche. Previous studies have suggest that diet rich in fiber and isoflavones may delay timing of puberty by increasing sex hormone-binding globulin and decreasing endogenous estrogens [ 28 , 45 ] among girls. Conversely, intake of SSB may contribute to high levels of insulin secretion and insulin-like growth factor1 (IGF-1), which could result in early onset of puberty [ 19 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary indices [ 27 ], which measure the extent to which current dietary recommendations are met, can thus provide additional insight into the effect of diet as a whole. To date, two prospective observational studies suggested that US girls with higher adherence to Mediterranean-like diet [ 28 ] as well as German children with higher overall diet quality according to German dietary recommendation [ 29 ] reached their puberty onset later. To date, one dietary index [ 30 ] has been developed for Chinese children, Chinese Children Dietary Index (CCDI), which measures adherence to current dietary recommendations [ 31 ] and could, thus, be used to analyze associations between pre-pubertal diet quality and timing of puberty in Chinese children.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the vegetarian diet, the Mediterranean diet is high in plant-based foods such as fiber-rich whole grains, vegetables, fruit, nuts, and fish, but limits red meat and processed foods. Szamreta et al (2020) studied the relationship between Mediterranean diet and age at menarche in the United States of America through the Jersey Girl Study, a longitudinal cohort study of 202 girls aged 9-10 years. Dietary intake was assessed using the 24-hour Food Recall method for at least 3 different days and grouped them into high, medium, and low Mediterranean Diet Scores.…”
Section: Mediterranean Diet and Age At Menarchementioning
confidence: 99%
“…Only one study specifically focused on the relationship between MD and the onset of puberty in the pediatric population. Szamreta et al [236] demonstrated that close adherence to the MD could decrease the risk of PP in a 9-10-year-old cohort of girls in New Jersey. In particular, a significantly reduced likelihood of breast development and a later age of menarche were observed compared to girls with poor MD adherence.…”
Section: Dietary Patterns Mediterranean Dietmentioning
confidence: 99%